Aprendizagem por exclusão em indivíduo com diferentes perfis de desenvolvimento - Langsdorff, Luiza Augusta de Oliveira Costa (2013)
It is noticed that children learn about 14.000 words to the age of five years old. One of the phenomenon related to this remarkable language development is known as exclusion responding. This responding, described as the immediate selection of an undefined comparison stimulus given and also undefined stimulus, excluding familiar stimuli, is being robustly verified among different populations. It s been also noticed that learning the relation between the new stimuli does not seem to occur through a single exclusion trial. However, exclusion trials have revealed itself an efficient procedure to teach new relations to individuals with typical and atypical development. This study, carried out with 22 participants where 8 had typical development, 11 had autism and 3 had Down syndrome and ages five to 46 years old, investigated, from a particular set of procedures and learning tests, the number of exclusion trials needed for the participants to learn the relations between undefined figures and undefined dictated names. At each trial, the researcher said a word and the participant selected one figure out of three that he/she considered correct. The procedure consisted of five phases: base line (1), introduction of the mask as neutral stimulus (2), exclusion trials (3), learning tests (4) and a nomination test (5). Phases 3 and 4 were repeated until learning was observed or until the number of 10 repetitions was reached. The procedure was replicated for four times, and the relations between the undefined dictated words Mido, Fani, Duca, Pagu and its respective figures were teached. All participants completed phases 1 and 2; 21 participants responded by exclusion; 19 participants learned all the relations presented. Concerning the amount of exclusion trials needed for learning the relation between new dictated names and figures, it was observed that a variation from 2 (the minimum programmed by the procedure) to 10 trials were needed for the learning of each stimuli pair to occur. Despite the relative variation, it is clear that the data were mostly concentrated on the minimum number of repetitions (2) and this was the trend line observed for the learning of all the stimuli pairs. The observed average was 2,1 trias for two of the stimuli pairs (Pagu and Duca) with standard deviations equal to 0,1. For the learning of Mido and Fani were needed, in average, 2,6 and 3,2 exclusion trials, with standard deviations 1,8 and 0,9 respectively. It is considered that the experimental conditions favored the learning outcomes and the typically used procedure can be configured in a kind of teaching technology of arbitrary relations and widely used in different educational contexts.